1998
DOI: 10.1051/aas:1998115
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution of neutral and ionic constituents in comet P/Halley

Abstract: Abstract. Multislit spectra of comet P/Halley were obtained on April 10, 1986, using a focal reducer with a field of ≈ 0.5• angular diameter. The number and arrangement of the slits allowed a reconstruction of the spatial distribution of principal neutral and ionic coma constituents within a frame of about 4 10 5 × 4 10 5 km 2 at the comet. Radial profiles and two-dimensional maps for the dust continuum, CN, C 3 , CH, CO + , and especially CO + 2 , are presented in absolute intensity and column density units, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 35 publications
0
1
0
1
Order By: Relevance
“…Так, типи речовини iонiв часто називають типами речовини хвоста. Проте, необхiдно вiдмiтити, що багато iонiв спостерiгаються вiдносно близько вiд ядра комети (гарною iлюстрацiєю є отриманi з довгою щiлиною спектри CO + i CO + 2 в кометi 1Р/Галлея [97]). Домiнуючими процесами для утворення iонiв є фотодисоцiацiя (наприклад, H 2 O+hν → OH + + H+e) i фотоiонiзацiя (наприклад, H 2 O + hν → H 2 O + + e) [98].…”
Section: основнI молекулярнI смуги в спектрах кометunclassified
“…Так, типи речовини iонiв часто називають типами речовини хвоста. Проте, необхiдно вiдмiтити, що багато iонiв спостерiгаються вiдносно близько вiд ядра комети (гарною iлюстрацiєю є отриманi з довгою щiлиною спектри CO + i CO + 2 в кометi 1Р/Галлея [97]). Домiнуючими процесами для утворення iонiв є фотодисоцiацiя (наприклад, H 2 O+hν → OH + + H+e) i фотоiонiзацiя (наприклад, H 2 O + hν → H 2 O + + e) [98].…”
Section: основнI молекулярнI смуги в спектрах кометunclassified
“…11 Results from the neutral mass spectrometer experiment onboard the Giotto spacecraft demonstrated that CO was produced by a distributed source near the nucleus rather than directly from the nucleus. 11 Results from the neutral mass spectrometer experiment onboard the Giotto spacecraft demonstrated that CO was produced by a distributed source near the nucleus rather than directly from the nucleus.…”
Section: Introductionmentioning
confidence: 99%